Human gut microbiome in human immunodeficiency virus and acquired immunodeficiency syndrome‐related diseases: Clinically relevant observations - Jordan A. Higgs; Kevin D. Seely; Amanda E. Brooks (Wiley, 2022)
Abstract The implications of recent discoveries pertaining to immune‐mediated disease and the human gut microbiome are vast. In a symbiotic relationship, the immune system modulates the maintenance of host‐microbe normobiosis, and the gut microbiome plays a critical role in developing and maintaining the host's innate and adaptive immune systems. The cutting edge of microbiome research and personalized medicine targets the clinical application and exploitation of gut microbiota modulation in the setting of specific diseases. For example, prebiotic/probiotic supplementation, microbiome enhancing diets, and fecal microbiota transplant have been studied as potential ameliorative supplemental interventions to combined antiretroviral therapy (cART) in human immunodeficiency virus‐positive (HIV+) individuals. Furthermore, recent evidence shows a positive correlation between improved CD4+ cell counts in HIV+ individuals and improved gut microbiota profile after cART. We supplement this finding with data and supporting evidence from recent studies to aid in the clinical application of these findings in this commentary. Preliminary data support the consideration of the gut microbiota in the proactive management of HIV‐associated comorbidities.